2007
DOI: 10.1248/jhs.53.142
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Triphala during Experimentally Induced Noise Stress in Albino Rats

Abstract: Stress is a term that generally has a negative connotation, which results in immune dysfunction. In this study, immunomodulatory effect of Triphala (equal proportion of Terminalia chebula, Terminalia bellerica and Emblica officinalis) during noise-stress in male albino rats was evaluated by analyzing the antibody titer, cytokines IL-2-Interleukin (2), IL-4 and IFN-Interferon (gamma) and Pan T, CD4 + /CD8 + lymphocyte phenotype in spleen. Four groups of rat were employed namely control, Triphala (1 g/kg body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…Such an increase in IL-4 and a concomitant decrease in IL-2 and IFN-γ on exposure to noise stress has been reported. 41 Our observations revealed that the deviated levels of the IL-4 and IFN-γ in chronically stressed rats were reversed by AC as well as α-asarone treatments while the IL-2 levels, though were markedly increased from the stressed animals, could not be completely reversed.…”
Section: Two Subsets Of T Helper Cells (Th Cells) Namelymentioning
confidence: 53%
“…Such an increase in IL-4 and a concomitant decrease in IL-2 and IFN-γ on exposure to noise stress has been reported. 41 Our observations revealed that the deviated levels of the IL-4 and IFN-γ in chronically stressed rats were reversed by AC as well as α-asarone treatments while the IL-2 levels, though were markedly increased from the stressed animals, could not be completely reversed.…”
Section: Two Subsets Of T Helper Cells (Th Cells) Namelymentioning
confidence: 53%
“…The present observation in noise stressed animal is further correlated with Srikumar et al. [24], where noise stress induced a decrease in FPT with an enhancement in LMI. The decrease in foot pad thickness after stress could be due to the effect of stress on the inflammatory, mediatory and adhesion molecules on the endothelial cell and extra vascular space.…”
Section: Discussionmentioning
confidence: 97%
“…During the experiment, the noise level peaked at 100 dB immediately after the generator was switched on and continued daily for 4 h for 15 days. The controls were also kept in these cages without noise stress exposure [24].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore the herb may cause augmentation of the humoral immune response to sheep red blood cells SRBCs acting as antigens that caused enhanced responsiveness of T and B-lymphocyte subtypes of the immune system thus promoting the anti-body synthesis (Sharififar et al, 2009) in the Wistar albino rats similar to what has been observed in other studies. The increased adhesion of the neutrophils to nylon fibers could be due to the compounds in the herb that may improve the migration of phagocytes such as neutrophils to the foreign body in blood vessels (Guyton and Hall, 2006;Srikumar et al, 2007). The neutrophils represent a multifunctional cell type in innate immunity that contributes to bacterial clearance by recognition, phagocytosis and killing of foreign bodies (Guyton and Hall, 2006;Srikumar et al, 2007), whereas the T and Blymphocytes are involved and responsible for production of antibodies leading to enhancement of immunity (Guyton and Hall, 2006;Srikumar et al, 2007;GarlandScience, 2008;Soehnlein et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The increased adhesion of the neutrophils to nylon fibers could be due to the compounds in the herb that may improve the migration of phagocytes such as neutrophils to the foreign body in blood vessels (Guyton and Hall, 2006;Srikumar et al, 2007). The neutrophils represent a multifunctional cell type in innate immunity that contributes to bacterial clearance by recognition, phagocytosis and killing of foreign bodies (Guyton and Hall, 2006;Srikumar et al, 2007), whereas the T and Blymphocytes are involved and responsible for production of antibodies leading to enhancement of immunity (Guyton and Hall, 2006;Srikumar et al, 2007;GarlandScience, 2008;Soehnlein et al, 2008). The observed increase in the footpad thickness of the Wistar albino rats which is a measure of the DTH as a result of the challenge of the SRBC antigens could be due to some of the compounds found in the herbal extract.…”
Section: Discussionmentioning
confidence: 99%